Digital Transformation of Retail Business Strategy - Končar, Jelena; Vučenović, Sonja; Marić, Radenko (International Scientific Conference Strategic Management and Decision Support Systems in Strategic Management, 2020)
Retailing will change in the next decade, more than in the past half-century. The biggest reason for this is precisely the digitization that is significantly changing service industries. Under the influence of digitalization there is an overall transformation of retailers’ business strategy. The problem and goal of this research is to identify key digital retail strategies that have the prospect of market success. New digital tactics and tools enable retailers to interact directly with consumers, enhance the shopping experience and track consumers at every point in the buying process. Digital transformation is revolutionizing retailing by transforming business models of retailers. Retailers who successfully implement a digital strategy have a chance in a new market game, those who do not pay attention to new trends risk losing the battle not only with the competition, but also with the time. Digitization involves not only technology but also the whole way of thinking and running a business. As a result of the research, recommendations of digital strategies will be presented to transform the retail business strategy in the modern digital era.